(untitled) (Comprehensive Journal of Science, 2025)
This study examines the geopolitical significance of strategic maritime straits and their role in reshaping regional and international balances, through a dual case study of the Strait of Hormuz and the Strait of Gibraltar. These two exemplars highlight how geographical, political, and economic factors intersect to determine loci of influence and control. The research underscores the vital status of such passages as arterial corridors for global trade and energy, and as contact points where the interests of major and regional powers converge. The findings indicate that control over—or influence within—maritime straits constitutes a strategic instrument with tangible effects on the international balance of power. They also show that differences in the surrounding geographical and political contexts produce distinct patterns of competition and conflict, making the security of these straits a central pillar in the stability of both regional and international orders.